2022
DOI: 10.3390/ijms23031363
|View full text |Cite
|
Sign up to set email alerts
|

The Human Gut Microbiome as a Potential Factor in Autism Spectrum Disorder

Abstract: The high prevalence of gastrointestinal (GI) disorders among autism spectrum disorder (ASD) patients has prompted scientists to look into the gut microbiota as a putative trigger in ASD pathogenesis. Thus, many studies have linked the gut microbial dysbiosis that is frequently observed in ASD patients with the modulation of brain function and social behavior, but little is known about this connection and its contribution to the etiology of ASD. This present review highlights the potential role of the microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 141 publications
0
43
0
Order By: Relevance
“…Cobalamin or B12 deficiency can cause increased homocysteine, or hyperhomocysteinemia, which occurs commonly in patients with inflammatory bowel disease (63). Similar changes in the gut microbial ecosystem in ASD studies showed the implications of gut dysbiosis in the production and utilization of vitamins such as B12 (64). The use of comparisons between AS and ASD that lead to microbial dysbiosis and metabolic disparities has the potential to identify what changes in the metabolome and microbiome contribute to disease severity.…”
Section: Discussionmentioning
confidence: 86%
“…Cobalamin or B12 deficiency can cause increased homocysteine, or hyperhomocysteinemia, which occurs commonly in patients with inflammatory bowel disease (63). Similar changes in the gut microbial ecosystem in ASD studies showed the implications of gut dysbiosis in the production and utilization of vitamins such as B12 (64). The use of comparisons between AS and ASD that lead to microbial dysbiosis and metabolic disparities has the potential to identify what changes in the metabolome and microbiome contribute to disease severity.…”
Section: Discussionmentioning
confidence: 86%
“…Gut bacteria were largely overlooked until they were found to be closely related with various gut or gutrelated disorders, such as irritable bowel syndrome [36][37][38], infectious diarrhea [39], ulcerative colitis, colorectal cancer, liver diseases, and obesity related disorders [40,41]. In addition, gut bacteria can be utilized as a medication strategy [42][43][44][45][46], including fecal microbiota transplantation (FMT) [47][48][49][50][51][52]. Gut bacteria recently became an explosive topic, going through roughly three development stages: (1) Feces microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial metabolites can act as neurotransmitters. Thus, in addition to the classic diseases associated with alterations in the microbiota, the microbiota is also related to central nervous system conditions, ie, autism, anxiety, and depression [48][49][50].…”
Section: Human Gut Microbiotamentioning
confidence: 99%